PENERAPAN SYARIAT ISLAM DALAM LINTASAN SEJARAH DAN HUKUM POSITIF DI INDONESIA - John Kenedi (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2017)
Indonesia is a country that  provides the widest  opportunity for its citizens to embrace and  run  the religious syariat.Sebagai country with the largest  Muslim population in the world, it is proper that the Muslim population dream of the realization of the application of Islamic Shari’ah in all joints of life. Application of Islamic Shari’a partially in every region of archipelago ever occurred during the reign  of the empire. Reflecting on past  successes, the same  effort con- tinues in various phases of the history  of the Indonesian nation from the era of independence to the Reformation era. Recorded various theories ever made by the legal experts with regard to the existence of Islamic Sharia  in the country. Starting from the theory of ReceptieinComplexu by van den Berg, followed  by Receptie and  Receptie Exit theory, each of which  was initiated by Snouck  Hurgronje and  Hazairin, to the  theory of Receptiea Contrario which  was born from the thought of Sajuti Thalib, including and Existence theory which became the concept of Islamic law enforcement in in the legal system of Indonesia. The latter theory is constantly being used in legitimizing the application of Islamic Sharia in Indonesia. Through the structural and  cultural approach coupled with the use of its supporting factors, there is still hope for Muslims to realize his ideals. Issuance of Regional Regulations with nuances of Islam is a tendency that is done by every region that envisions the enforcement of Islamic Shari’a. However, such structural approaches still have prob- lems which require a law that can be specifically used  as the basis for ensuring that Islamic Shari’a law can be applied